Algorithms for the identification of three-dimensional maximal common substructures - Brint, Andrew T; Willett, Peter (Journal of chemical information and computer sciences, 1987)
2 algorithms are described for the identification of the maximal substructures common to 2 (or more) 3-dimensional chemical structures, where a substructure consists of a set of atoms and the associated interatomic distances.